Associations of leukocyte telomere length with aerobic and muscular fitness in young adults - Williams, DM; Buxton, JL; Kantomaa, MT; Tammelin, TH; Blakemore, AIF; Järvelin, MR (American Journal of Epidemiology, 2017)
Decline in both telomere length and physical fitness over the life course may contribute to increased risk of several chronic diseases. The relationship between telomere length and aerobic and muscular fitness is not well characterized. We examined whether there are cross-sectional associations of mean relative leukocyte telomere length (LTL) with objective measures of aerobic fitness, muscle strength, and muscle endurance, using data on 31-year-old participants of the Northern Finland Birth Cohort 1966 (n = 4,952-5,205, varying by exposure-outcome analysis). Aerobic fitness was assessed by means of heart rate measurement following a standardized submaximal step test; muscular fitness was assessed by means of a maximal isometric handgrip strength test and a test of lower-back trunk muscle endurance. Longer LTL was associated with higher aerobic fitness and better trunk muscle endurance in models including adjustment for age, sex, body mass index, socioeconomic position, diet, smoking, alcohol consumption, physical activity level, and C-reactive protein. In a sex-stratified analysis, LTL was not associated with handgrip strength in either men or women. LTL may relate to aspects of physical fitness in young adulthood, but replication of these findings is required, along with further studies to help assess directions and causality in these associations. This work was supported financially by the following institutions: the Academy of Finland (grants 104781, 120315, 129269, 1114194, and 12926); University Hospital Oulu, Biocenter, University of Oulu (grant 75617); the European Commission (grant QLG1-CT-2000-01643); the National Heart, Lung, and Blood Institute, US National Institutes of Health (grant 5R01HL087679-02); the National Institute of Mental Health, US National Institutes of Health (grant 5R01MH63706:02); the Medical Research Council, United Kingdom (grants G0500539 and G0600705); the Wellcome Trust, United Kingdom (grant GR069224); and Diabetes UK (grant 08/0003775). J.L.B. was supported by a Wellcome ...